2012
DOI: 10.1186/1471-230x-12-175
|View full text |Cite
|
Sign up to set email alerts
|

Dyspeptic symptoms and delayed gastric emptying of solids in patients with inactive Crohn’s disease

Abstract: BackgroundPatients with Crohn’s disease (CD) have been shown to present dyspeptic symptoms more frequently than the general population. Some of these symptoms could be related to motility disorders to some degree. Then, we propose to investigate whether gastric emptying of solids in patients with inactive CD is delayed and to determine the relationships between gastric emptying and dyspeptic symptoms in inactive CD.MethodsTwenty-six patients with inactive Crohn’s disease, as defined by a Crohn’s Disease Activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…These new findings apparently contrast with earlier studies reporting delayed gastric emptying in patients with inactive IBD: Nobrega et al [5] reported a similar proportion of CD patients with delayed gastric emptying in remission as we only saw in active disease. This discrepancy is probably explained by the fact that Nobrega et al used the conventional CDAI threshold (> 150) for definition of active vs. inactive CD.…”
Section: Discussioncontrasting
confidence: 99%
“…These new findings apparently contrast with earlier studies reporting delayed gastric emptying in patients with inactive IBD: Nobrega et al [5] reported a similar proportion of CD patients with delayed gastric emptying in remission as we only saw in active disease. This discrepancy is probably explained by the fact that Nobrega et al used the conventional CDAI threshold (> 150) for definition of active vs. inactive CD.…”
Section: Discussioncontrasting
confidence: 99%
“…The degree to which this dysmotility improves following treatment or remission of CD has been studied less, partly because of the relative difficulty and inconvenience of manometric measurements. Although the available literature suggests that there are detectable small bowel and gastric motility disturbances even in inactive CD, these studies compared motility in CD patients with healthy controls rather than within the same individual after treatment. We are not aware of any intra‐individual comparisons of motility pre‐ and post‐treatment in CD.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 11 , in which cine magnetic resonance enterography (MRE) was employed in addition to the regular MRI protocol, found that imaging areas of altered gut motility helped to detect more CD-specific findings. Other studies have shown that CD is associated with delayed gastric emptying, possibly due to inflammation 12 .…”
Section: Discussionmentioning
confidence: 93%